A campanha Diretas Já e a transição brasileira da ditadura militar para a democracia burguesa - Nery, Vanderlei Elias (2012)
This thesis aims to analyze the campaign Diretas Já linking it to the Brazilian transition from military dictatorship to bourgeois democracy. We start from a Marxist definition of theState capitalist,the form of and political regime State, for from this theoretical concept to analyze the campaign Diretas Já. It is our goal to reconstruct the trajectory of the campaign, as well as the role of social classes and political parties to demonstrate how the bourgeois opposition leads the campaign, imposed a form of organization, filter the whole process of struggle for the Congress, with as single focus, the approval of the Dante de Oliveira amendment. We intend to demonstrate how the form of campaign organization Diretas Já imposed by the bourgeois opposition and accepted by the left parties and unions, prevented the labor movement and could use popular forms of struggle that confront capital and labor. From a Marxist conception of democracy and citizenship, we demonstrate the limits of institutionalist analysis, which state that the Diretas Já has been the rebirth of civil society and citizenship, consolidating an expansion of political and social rights